Security challenges in Central Europe, 1848–1849 - Molnar Fedir; Molnár Ferenc; Молнар Федір; Orosz Melánia; Орос Меланія (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The revolutionary years of 1848–1849 profoundly reshaped the political and social order of Central Europe, generating a complex set of security challenges that affected the Habsburg Monarchy and, within it, the Kingdom of Hungary and its surrounding regions. The collapse of imperial administrative structures, the rise of modern national movements, and the increasing involvement of great powers fundamentally transformed the security environment of the region. In this period, security cannot be understood solely in military terms; it encompassed political legitimacy, state sovereignty, ethnic coexistence, and social stability, all of which were simultaneously questioned and renegotiated [1]. With the outbreak of the revolution, the previously stable administrative system of the Habsburg Empire began to disintegrate at an unexpected pace. The authority of Vienna was shaken, the links between central and regional governance weakened, and a power vacuum emerged in many multiethnic areas [3]. Although the Hungarian government attempted to build a modern constitutional state, the rapid implementation of reforms and the unstable political environment heightened the likelihood of armed conflict [5]. As imperial authority weakened, local populations found themselves increasingly vulnerable: deficiencies in law enforcement, logistical shortages, and administrative uncertainty all contributed to the region’s fragile security situation. The strengthening of national movements fundamentally shaped the security landscape of mid19th-century Central Europe. Hungarian, Croatian, Serbian, Romanian, and Slovak political elites followed divergent state-building agendas, leading to conflicts in which self-organised armed groups, national guards, and militias played a key role. These formations created parallel centres of authority, challenging state control and exposing the civilian population to new risks. National conflicts frequently escalated into ethnic tensions, exacerbated by communication gaps, political mistrust, and differing interpretations of loyalty. In such a multiethnic environment, the question of security was intertwined with competing national aspirations and fears [5]. Great power intervention represented another decisive security factor. From late 1848 onwards, the Habsburg government increasingly turned toward military measures, while preparations for Russian intervention began early in 1849. The eventual entry of the Russian imperial army not only sealed the fate of the Hungarian struggle for independence but also demonstrated the vulnerability of Central European regions to external geopolitical interests. The security of the region depended not only on internal stability but also on the strategic calculations of major powers [4]. This intervention cemented the role of Central Europe as a geopolitical buffer zone, a status it retained well into the second half of the nineteenth century.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: 1848–1849 revolutions; Central European security; multiethnic conflict